The United States Does CAIR About Cultural Safety: Examining Cultural Safety Within Indigenous Health Contexts in Canada and the United States. (May 2017) - Darroch, Francine; Giles, Audrey; Sanderson, Priscilla; Brooks-Cleator, Lauren; Schwartz, Anna; Joseph, Darold; Nosker, Roger
Purpose: This article examines the concept and use of the term cultural safety in Canada and the United States.Design: To examine the uptake of cultural awareness, cultural sensitivity, cultural competence, and cultural safety between health organizations in Canada and the United States, we reviewed position statements/policies of health care associations.Findings: The majority of selected health associations in Canada include cultural safety within position statements or organizational policies; however, comparable U.S. organizations focused on cultural sensitivity and cultural competence.Discussion: Through the work of the Center for American Indian Resilience, we demonstrate that U.S. researchers engage with the tenets of cultural safety—despite not using the language.Conclusions: We recommend that health care providers and health researchers consider the tenets of cultural safety.Implications for Practice: To address health disparities between American Indian populations and non–American Indians, we urge the adoption of the term and tenets of cultural safety in the United States.